The paramedic companion - Arthur Hsieh (McGraw-Hill, 2009)
The Paramedic Companion: A Case-based Worktext is a nontraditional workbook that can be used throughout the paramedic curriculum and is tightly integrated with the main textbook. The Paramedic Companion goes beyond the simple review and test